Sea shell diversity and rapidly evolving secretomes: insights into the evolution of biomineralization. Issue 1 (December 2016) - Kocot, Kevin; Aguilera, Felipe; McDougall, Carmel; Jackson, Daniel; Degnan, Bernard
Abstract An external skeleton is an essential part of the body plan of many animals and is thought to be one of the key factors that enabled the great expansion in animal diversity and disparity during the Cambrian explosion. Molluscs are considered ideal to study the evolution of biomineralization because of their diversity of highly complex, robust and patterned shells. The molluscan shell forms externally at the interface of animal and environment, and involves controlled deposition of calcium carbonate within a framework of macromolecules that are secreted from the dorsal mantle epithelium. Despite its deep conservation within Mollusca, the mantle is capable of producing an incredible diversity of shell patterns, and macro- and micro-architectures. Here we review recent developments within the field of molluscan biomineralization, focusing on the genes expressed in the mantle that encode secreted proteins. The so-called mantle secretome appears to regulate shell deposition and patterning and in some cases becomes part of the shell matrix. Recent transcriptomic and proteomic studies have revealed marked differences in the mantle secretomes of even closely-related molluscs; these typically exceed expected differences based on characteristics of the external shell. All mantle secretomes surveyed to date include novel genes encoding lineage-restricted proteins and unique combinations of co-opted ancient genes. A surprisingly large proportion of both ancient and novel secreted proteins containing simple repetitive motifs or domains that are often modular in construction. These repetitive low complexity domains (RLCDs) appear to further promote the evolvability of the mantle secretome, resulting in domain shuffling, expansion and loss. RLCD families further evolve via slippage and other mechanisms associated with repetitive sequences. As analogous types of secreted proteins are expressed in biomineralizing tissues in other animals, insights into the evolution of the genes underlying molluscan shell formation may be applied more broadly to understanding the evolution of metazoan biomineralization.